Comparison of Ziehl-Neelsen staining microscopy and immunochromatographic tuberculosis test for diagnosis of pulmonary tuberculosis - Rai, DR; Kshetry, NT; Bhargava, D; Pokhrel, BM (Journal of Institute of Medicine Nepal, 2007)
Background: Tuberculosis continues to be a great public health problem in Nepal. The evaluation of suitable diagnostic method to diagnose tuberculosis is urged. Methods: Three consecutive early morning sputum collected from413 patients were subjected to ZN staining and serum from 224 patients to ICT-TB test. Results: Overall positive results of Z-N staining and ICT-TB test were 13.1%and 14.3%, respectively. In ICT-TB test, males were found more positive (14.7%) than females (13.9%)(P>0.05) but in microscopy, it was vice-versa (P>0.05).Age group 41-60 was significantly more seropositive compare to younger, however, in combination it wasn’t significant (P>0.05). Alcoholics were significantly high (25.5%)(P<0.05) and smokers were marginally high (17.3%) (P>0.05)AFB positive compared to non alcoholics (11.5%) and non-smokers (11.6%). Students and service men were remarkably lower AFB positive compare to farmers and workers but interestingly nobody was found positive among business personnel (P>0.05). Conclusion: Z-N staining microscopy is cheaper and equally sensitive hence it is more useful diagnostic tool than ICT-TB test for pulmonary tuberculosis. Key words: Pulmonary Tuberculosis, Ziehl-Neelsen staining, ICT-TB test, Nepal The full text of this paper is available at Journal of Institute of Medicine website